2017
DOI: 10.1161/jaha.116.004766
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Evidence That the Tissue Doppler Index E/e′ Reflects Left Ventricular Filling Pressure Changes After Exercise or Pharmacological Intervention for Evaluating Diastolic Function? A Systematic Review

Abstract: BackgroundNoninvasive echocardiographic tissue Doppler assessment (E/e′) in response to exercise or pharmacological intervention has been proposed as a useful parameter to assess left ventricular (LV) filling pressure (LVFP) and LV diastolic dysfunction. However, the evidence for it is not well summarized.Methods and ResultsClinical studies that evaluated invasive LVFP changes in response to exercise/other interventions and echocardiographic E/e′ were identified from PubMed, Scopus, Embase, and Cochrane Librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 66 publications
2
48
2
Order By: Relevance
“…This is not always doable for breast cancer patients with expanders or prostheses. Moreover, we considered that E/E' does not help to diagnose DD in patients with preserved LVEF [21,22]. Here, patients diagnosed with grade I DD by E/A and DT did not develop E/E' abnormalities, which was consistent with this notion.…”
Section: Study Limitations and Strengthssupporting
confidence: 82%
“…This is not always doable for breast cancer patients with expanders or prostheses. Moreover, we considered that E/E' does not help to diagnose DD in patients with preserved LVEF [21,22]. Here, patients diagnosed with grade I DD by E/A and DT did not develop E/E' abnormalities, which was consistent with this notion.…”
Section: Study Limitations and Strengthssupporting
confidence: 82%
“…Regarding the use of effort‐related diastolic dysfunction as a predictor of coronary restenosis, Gibby and Burgess et al demonstrated that predefined cutoffs for postexercise E / e' > 13 had moderate sensitivity and good specificity for identifying elevated LVFP . In contrast, a recent systematic review suggested that current evidence is insufficient to conclude that E/e' is reliable for assessing LVFP changes in response to exercise or other interventions . In the current study, the mean values for both pre‐ and post‐TET E/e' were lower than 13 in the restenosis group.…”
Section: Discussioncontrasting
confidence: 59%
“…found E/e’ useful in improving identification of patients with HFpEF (Obokata et al ., ). However, changes in E/e’ failed to correlate with LA or LV pressures in most studies (Choi et al ., ; Manouras et al ., ; Bhella et al ., ; Santos et al ., ), irrespective of LV systolic function (Sharifov & Gupta, ). This concludes that E/e’ at both rest and exercise cannot be relied on to reflect changes in filling pressures, in patients other than those in end‐stage heart failure (Nagueh et al ., ; Ommen et al ., ).…”
Section: Discussionmentioning
confidence: 99%